The Role of Safety Beliefs in Influencing Safety Outcomes in the Mining Sector in South American Countries - Andrei, Daniela; Griffin, Mark; Cham, Belinda; Opacic, Jelena; Diaz, Raul; Ochoa, Paola (IM4DC, 2015)
The aim of this follow-up research was to: • develop a more refined measurement of individual safety beliefs, to allow an improved understanding of how safety beliefs influence safety related outcomes in the mining sector in South America • complement the existing data for Asia-Pacific and African countries collected through the ‘International Safety Benchmark’ survey, with new data from South American countries